Transformasi Identitas Administratif dan Tata Kelola Hibrida: Negosiasi Otoritas Birokrasi dan Adat di Kabupaten Bungo, Indonesia - Mulia Jaya; Dedi Epriadi; Didik Try Putra (Research and Development Agency Ministry of Home Affairs, 2025)
These days, local governments keep running into friction between official bureaucracy and the deep-rooted customs of their communities. In Bungo Regency, Indonesia, this tension really came to the surface after Local Regulation No. 9 of 2007 swapped out the term “Village Head” for the traditional title “Rio.” This study examines how that change has shaken up how local leaders see themselves and how they operate. I took a close look at Bungo through interviews with 25 key people, combed through legal documents, and even hung out (virtually) in the “Pesan Bungo” WhatsApp group to see how things play out day to day. The big questions: How do these local leaders juggle their official duties and their traditional roles? What does this new title actually change on the ground? And what should policymakers take away from all this? Here’s what I found. The Rio isn’t just picking a side—they’re constantly switching hats, sometimes acting by the book, leaning into tradition, and often working behind the scenes through informal networks. They’re like fixers, piecing together Solutions from whatever’s at hand. On one hand, using the Rio title boosts their credibility with both the government and the local community. It gives them more room to maneuver and negotiate what leadership means. But there’s a flip side: it can also concentrate power in a few hands and turn tradition into just another tool for influence. Bottom line? Changing administrative titles isn’t just a surface-level move. It turns local government into a battleground for power and meaning. If public value and inclusivity matter, then governance needs to stay flexible and responsive—ready to adapt as these tensions play out.